2014
DOI: 10.1039/c4tc00480a
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Ga auto-incorporation in nominal InAlN epilayers grown by MOCVD

Abstract: We report on the consistent measurement of gallium incorporation in nominal InAlN layers using various complimentary techniques, underpinned by X-ray diffraction. Nominal InAlN layers with similar growth conditions were prepared, and the change in unintended Ga content in the group III sublattice ranged from $24% to $12% when the total reactor flow rate was increased from 8000 to 24 000 standard cubic centimetres per minute. Ultra-thin InAlN/GaN HEMT layers were grown in a clean reactor to minimize Ga auto-inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 25 publications
(46 reference statements)
3
20
0
Order By: Relevance
“…These results are consistent with several studies in the literature reporting parasitic Ga-incorporation in Al 1−x In x N layers where the exact Ga-profiles will depend on the history of previous growth runs in the reactor [35,[55][56][57][58][59][60]. InN content derived from XRD using Vegard's rule [27] or the modified Vegard's rule described by equation (1) [30] as a function of the InN content measured by RBS for sample series C (a), S (b) and T (c).…”
Section: Compositional Analysissupporting
confidence: 82%
See 1 more Smart Citation
“…These results are consistent with several studies in the literature reporting parasitic Ga-incorporation in Al 1−x In x N layers where the exact Ga-profiles will depend on the history of previous growth runs in the reactor [35,[55][56][57][58][59][60]. InN content derived from XRD using Vegard's rule [27] or the modified Vegard's rule described by equation (1) [30] as a function of the InN content measured by RBS for sample series C (a), S (b) and T (c).…”
Section: Compositional Analysissupporting
confidence: 82%
“…Possibly such anomalous behaviour can also be explained by hydrostatic strain introduced by defects or by impurities. In particular, Ga contamination features in the literature on MOCVD growth of Al 1-x In x N films [35,[55][56][57][58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…Growth was performed in an Aixtron 3 × 2 inch close‐coupled showerhead MOVPE reactor. Prior to the InAlN growth experiments, the reactor was long‐baked at 1250 °C and then coated with about 15 μm AlN at 1100 °C to prevent residual gallium that may auto‐incorporate in InAlN . Trimethylaluminum (TMAl), trimethylindium (TMIn), and ammonia (NH3) precursors were used as Al, In, and N sources, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…unwanted Ga in In Al 1− N layer of sample A that ruled out growth environment and lingering precursors for being the source of Ga in the transition region of sample B[37].It is found that In and Al-incorporation in 40 nm thick transition region is complementary to the diminishing Ga profile in the subsequent layer growth. On the contrary to sample A, no uniform region is observed in sample B.…”
mentioning
confidence: 87%